Anticonvulsant Study of Pongamia Pinnata Linn. Against Pentylenetetrazole Induced Convulsion in Rats - ASHISH MANIGAUHA; SUNITA PATEL (International Journal of Pharma and Bio Sciences, 2010)
The purpose of this study is to explore the anticonvulsant effect of the leaf extract of Pongamia pinnata using pentylene tetrazole induced convulsion (PTZ) in rats. Pongamia pinnata is an indigenous plant belonging to the family Fabaceae (Papilionaceae) commonly known as Karanj. Freshly powdered leaves were extracted with 70% ethanol. The convulsion is induced by administration of pentylene tetrazole (80 mg/kg, i.p.) to wistar albino rats and those showing response were divided into three groups of six animals each. The group I treated with 1% normal saline (1ml/100gm, orally), Groups II treated with phenytoin sodium (25 mg/kg, i.p.) and Groups III treated with ethanolic extract of PPLE at a dose of (250 mg/kg, i.p.). The ethanolic extract showed significant anticonvulsant activity by lowering the duration of extension phase (3.72 ± 0.65) when compared to control group (8.94 ± 0.42). From the experiment we can say Pongamia pinnata had significant anticonvulsant activity.